A Review of Building Energy Retrofit Measures, Passive Design Strategies and Building Regulation for the Low Carbon Development of Existing Dwellings in the Hot Summer–Cold Winter Region of China - Liu, Chenfei; Sharples, Stephen; Mohammadpourkarbasi, Haniyeh (Energies (Basel), 2023)
Retrofitting buildings to achieve improved levels of energy performance is a key strategy in the transition to a low-/net zero carbon future. In China, there has been an enormous growth in residential construction in recent decades in response to the country’s economic development and population growth. However, although these buildings are structurally solid and have long functional life spans, most have very poor thermal performance. Therefore, they would be very suitable for energy retrofitting. Because of the variety of retrofitting options, it is important to review the retrofit measures, regulations and possible outcomes to find effective, long-term solutions that strike a balance between the energy saved, the carbon emitted and the financial costs over a building’s lifetime. This paper reviews suitable retrofit measures for the hot summer–cold winter region of China, because this is an area with huge numbers of residential buildings that are suitable for energy retrofitting. The study explores the current conditions of targeted residential buildings, retrofit schemes, building regulations, and policy gaps towards achieving China’s 2060 carbon neutrality goal. The review indicates that current mandatory building energy regulations in this region are not ambitious enough to achieve a significantly lower carbon future, and one-step deep Passivhaus retrofit schemes are recommended to achieve decarbonization goals.